Purposeful Program Theory: Effective Use of Theories of Change and Log ic Models - Funnell, Sue C.; Rogers, Patricia J. (Wiley, 2011)
Between good intentions and great results lies a program theory—not ju st a list of tasks but a vision of what needs to happen, and how. Now widely used in government and not-for-profit organizations, program th eory provides a coherent picture of how change occurs and how to impro ve performance. Purposeful Program Theory shows how to develop, repres ent, and use program theory thoughtfully and strategically to suit you r particular situation, drawing on the fifty-year history of program t heory and the authors' experiences over more than twenty-five years."F rom needs assessment to intervention design, from implementation to ou tcomes evaluation, from policy formulation to policy execution and eva luation, program theory is paramount. But until now no book has examin ed these multiple uses of program theory in a comprehensive, understan dable, and integrated way. This promises to be a breakthrough book, va luable to practitioners, program designers, evaluators, policy analyst s, funders, and scholars who care about understanding why an intervent ion works or doesn't work." —Michael Quinn Patton, author, Utilization -Focused Evaluation"Finally, the definitive guide to evaluation using program theory! Far from the narrow 'one true way' approaches to progr am theory, this book provides numerous practical options for applying program theory to fulfill different purposes and constraints, and guid es the reader through the sound critical thinking required to select f rom among the options. The tour de force of the history and use of pro gram theory is a truly global view, with examples from around the worl d and across the full range of content domains. A must-have for any se rious evaluator." —E. Jane Davidson, PhD, Real Evaluation Ltd.Companio n Web site: josseybass.com/go/funnellrogers